(untitled) (International Journal of Scientific Trends, 2025)
This article investigates the language proficiency of three bilingual students representing different age groups, with a focus on assessing their overall language levels, as well as identifying their specific strengths and weaknesses across various language skills. Through a comprehensive analysis, the research aims to provide a deeper understanding of the individual learning processes and developmental trajectories of bilingual learners. Additionally, the study incorporates the researcher’s personal beliefs and expectations concerning bilingual education, highlighting the pedagogical implications of supporting bilingual students effectively. The findings reveal a range of challenges and advantages experienced by bilingual learners, underscoring the necessity for differentiated and context-sensitive instructional strategies to foster their linguistic and academic growth. This research contributes to the broader discourse on bilingualism by emphasizing the complexity of bilingual language development and the critical role of tailored educational interventions.